On the poorly known genus Anuvinda Lehtinen, 1967 (Araneae: Titanoecidae) - Almeida-Silva, Lina M.; Brescovit, Antonio D.; Griswold, Charles E. (Zootaxa, 2009)
The spider genus Anuvinda includes a single species described from India, Anuvinda escheri (Reimoser), based on a female. The male remained unknown and no other specimens beyond the type specimen are known. In this paper we present the first description of the male of A. escheri and the redescription of the female, based on material recently collected in China, Laos and Thailand. In addition, the distribution range of the species is extended to include these three countries.